Analysis of BAZNAS RI’s Financial Health Based on the IKOPZ for the 2020–2024 Period - Nadia Zahra; Qurroh Ayuniyyah; Nurman Hakim (Al-Infaq Jurnal Ekonomi Islam, 2026)
This study is motivated by the significant gap between the national zakat potential of IDR 327 trillion and its actual collection , further influenced by issues surrounding the credibility and public image of zakat management organizations. This research aims to analyze the financial health of the National Amil Zakat Agency (BAZNAS RI) as the central coordinating entity based on the Zakat Management Organization Health Index (IKOPZ) for the 2020–2024 period. A quantitative method with a descriptive approach was employed, utilizing secondary data from audited annual financial statements and official annual reports of BAZNAS RI. Financial performance was evaluated through five core IKOPZ indicators: activity ratio, efficiency ratio, amil fund ratio, liquidity ratio, and growth ratio. The results reveal that the overall financial performance of BAZNAS RI fell into the good and healthy category. In terms of activity, fund management was effective, despite a temporary decline in the Allocation to Collection Ratio (ACR) in 2023. The efficiency aspect demonstrated excellent performance, successfully reducing operational expenses to 1% while consistently maintaining amil rights at a stable 11%. The institution's liquidity was highly liquid in meeting short-term obligations. Meanwhile, the growth aspect displayed a positive yet fluctuating trend , notably a contraction in infaq/sadaqah growth in 2021 (-9%) which was resiliently countered by a massive surge in 2023 (151%). The implications of this study reaffirm the professionalism of BAZNAS RI's financial governance, serving as a fundamental asset to strengthen public trust to optimize national zakat potential absorption.